Proceso de Atención de Enfermería en paciente masculino de 63 años de edad con hipertrofia prostática benigna. - Trejo Vera, Génesis Tamara (2020)
Benign prostatic hypertrophy (BPH) is defined as an enlarged prostate that can cause difficulty at urination, causing urinary symptoms such as nicturia, incontinence, hematuria, two-stroke urination blocking bladder urine flow (Garcia, 2017). In some cases this disease can lead to infectious processes, bladder lithiasis and impaired complications of kidney function. It is important to mention that in order to identify this complication, a specific uroculture, prostate antigen or hematic biometrics examination must be performed. While drug treatment includes medications to relax the bladder or contract the prostate, and correction procedures such as prostatectomy (Garcia, 2017). The present clinical case aims to apply the Nursing Care Process in a 63-year-old male patient with a 30-day-evolving syntomatological picture, characterized by acute urinary retention. The patient requires hospitalization for definitive diagnosis of benign prostatic hypertrophy. The purpose of the application of the Nursing Care Process was possible to perform on the affected individual for the purpose of providing individualized comprehensive care, through the nursing interventions provided during his/her hospital stay, in order to achieve the complete well-being of the health state and return to his society.